Patients' Anxiety and Resilience: A Study in the Puskesmas Kasihan 1 Bantul Area - Hidayati, Laili Nur; Ikrima, Rai Rotun (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Puskesmas Kasihan 1 Bantul is one of the health centers that provide care and hospitalization for COVID-19 patients, with over 2300 data confirmed positive for the virus. COVID-19 caused anxiety in up to 63% of Indonesians, as well as fear of death and difficulties in managing emotions and relaxing. Therefore, psychological intervention to improve mental health is necessary. The study's focus was to see if there was a relationship between anxiety and resilience in COVID-19 patients. Method of quantitative research using a cross-sectional approach. A total of 103 people were sampled using a simple random sampling method. The Hamilton Anxiety Rating Scale (HAM-A) and Connor Davidson Resilience Scale (CD-RISC) questionnaires were employed in the study. This study included both univariate and bivariate analyses. According to the findings, 54 respondents (52.4%) reported having no anxiety, while 62 people reported having low resilience (60.2%). The study revealed a relationship between anxiety and resilience in patients with COVID-19, with r = -0.226 is a negative (-) or opposite direction of correlation and a significance value of 0.022 (p less than 0.05). In patients with COVID-19, there is a relationship between anxiety and resilience; the greater the resilience, the lower the respondents' anxiety. It is important to strengthen community resilience through informational support, emotional support, and rehabilitation. Abstrak: Puskemas Kasihan 1 Bantul merupakan salah satu puskesmas yang memberikan pelayanan dan rawat inap bagi pasien COVID-19, dalam satu tahun terakhir tercatat 2300 data terkonfirmasi positif COVID-19. Dampak COVID-19 di Indonesia menimbulkan ansietas sebanyak 63% disertai rasa khawatir akan kematian, sulit mengontrol emosi dan sulit rileks. Resiliensi sebagai intervensi psikologis yang bertujuan meningkatkan kesehatan mental. Tujuan Penelitian ini untuk mengetahui hubungan ansietas dengan resiliensi pada pasien riwayat COVID-19. Metode penelitian kuantitatif dengan desain cross sectional. Pengambilan sampel menggunakan simple random sampling sejumlah 103 responden. Instrumen penelitian menggunakan Kuesioner Hamilton Anxiety Rating Scale (HAM-A) dan Connor Davidson Resillience Scale (CD-RISC). Analisa penelitian menggunakan univariat dan bivariat. Hasil penelitian di dapatkan data ansietas baik sebanyak 54 responden (52,4%), resiliensi rendah sebanyak 62 responden (60,2%). Hasil analisis menunjukkan adanya hubungan antara ansietas dengan resiliensi pada pasien riwayat COVID-19 di wilayah Puskesmas Kasihan 1 Bantul, nilai signifikansi sebesar 0.022 (p kurang dari 0.05), r = -0.226 dengan arah korelasi negatif (-) atau berlawanan. Terdapat hubungan antara ansietas dengan resiliensi pada pasien dengan COVID-19 yang berarti semakin tinggi resiliensi semakin rendah ansietas pada responden. Ansietas meningkat pada puncak COVID-19 dengan resiliensi masyarakat cenderung pesimis perlu perhatian khusus sehingga di perlukan peningkatan resilensi masyarakat berupa dukungan informasional, dukungan emosional, dan keyakinan rehabilitasi.